PEMBUATAN PAKAN LELE DI USAHA KECIL MENENGAH BUDIDAYA IKAN LELE DI DESA MARGA AGUNG KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Hendra, Kadek; Eka Yusendra, Muhamad Ariza (IBI Darmajaya, 2015)
Marga Agung Village, which located at Jatiagung district, South Lampung has many developed SMEs (Small and Medium Enterprises) such as oyster mushroom, crickets, and catfish SMEs. Yet amidst those potential, Marga Agung Village has not fully optimize the knowledge or innovation in order to develop their SMEs. Like instance, the growing demand of catfish from culinary industry, supposed to be provide benefits to catfish SMEs, but the fact still does not meet expectations, because many Catfish Entrepreneus suffer a great loss to operate the business. Community service activities that we do focused on company owned by Mr. sugeng that engaged in breeding catfish. After some Survey and interview in catfish breeding company belonged to Mr. Sugeng, we find substantial problems, that is: catfish food bought from the market are too expensive, and because of that affected to the low income of catfish breeding company owned by Mr. Sugeng. The Solution that we have made, to solve the problems is to create artificial food as a cheap alternative and healthy feed for catfish, with Counselling methods and demonstrations.Keywords: Catfish SMEs, Catfish Breeding, Catfish Foods